Selective Vulnerability of the Cochlear Basal Turn to Acrylonitrile and Noise. (26th March 2009) - Pouyatos, B.; Gearhart, C. A.; Nelson-Miller, A.; Fulton, S.; Fechter, L. D.
Abstract : Exposure to acrylonitrile, a high-production industrial chemical, can promote noise-induced hearing loss (NIHL) in the rat even though this agent does not itself produce permanent hearing loss. The mechanism by which acrylonitrile promotes NIHL includes oxidative stress as antioxidant drugs can partially protect the cochlea fromacrylonitrile + noise . Acrylonitrile depletes glutathione levels while noise can increase the formation of reactive oxygen species. It was previously noted that the high-frequency or basal turn of the cochlea was particularly vulnerable to the combined effects of acrylonitrile and noise when the octave band noise (OBN) was centered at 8 kHz. Normally, such a noise would be expected to yield damage at a more apical region of the cochlea. The present study was designed to determine whether the basal cochlea is selectively sensitive to acrylonitrile or whether, by adjusting the frequency of the noise band, it would be possible to control the region of the auditory impairment. Rats were exposed to one of three different OBNs centered at different frequencies (4 kHz, 110 dB and 8 or 16 kHz at 97 dB) for 5 days, with and without administration of acrylonitrile (50 mg/kg/day). The noise was set to cause limited NIHL by itself. Auditory function was monitored by recording distortion products, by compound action potentials, and by performing cochlear histology. While the ACN-only and noise-only exposures induced no or little permanent auditory loss, the three exposures toacrylonitrile + noise produced similar auditory and cochlear impairments above 16 kHz, despite the fact that the noise exposures covered 2 octaves. These observations show that the basal cochlea is much more sensitive toacrylonitrile + noise than the apical partition. They provide an initial basis for distinguishing the pattern of cochlear injury that results from noise exposure from that which occurs due to the combined effects of noise and a chemical contaminant.